Songs for the Ego: Theorizing Musical Self-Enhancement - Elvers, Paul (Frontiers in Psychology, 2016)
This paper outlines a theoretical account of musical self-enhancement. I claim that listening to music serves as a resource for actively manipulating affective states so that a positive self-view is maintained and a sense of optimism is provided. Self-enhancement—the process by which individuals modify their self-worth and gain self-esteem—typically takes place in social interactions. I argue that experiencing music may serve as a unique “aesthetic surrogate” for interaction, which equally enables self-enhancement. This ability relies on three main characteristics of the musical experience, namely, its capacity to (a) evoke empathetic feelings, (b) elicit social cohesion and affiliation, and (c) elicit feelings of reward. I outline how these characteristics relate to theories of music cognition and empirical findings in psychology and neuroscience research. I also explain the specifics of musical self-enhancement and how it differs from music’s other regulatory functions such as mood- and emotion regulation. My aim in introducing the notion of musical self-enhancement is to broaden our understanding of how music functions as an environmental resource entailing access to unique affective states and how musical experiences are co-constituted by both the agent and the sonic environment. This specific use of music for self-enhancement can be regarded as a form of affective niche construction, providing the external conditions in which people can experience themselves more positively and maintain high self-esteem.